Fractura por fatiga de un tallo de revisión femoral modular cónico estriado de fijación distal. - Buttaro, Martin; Van Citters, Douglas; Carlson, Evan; Comba, Fernando; Slullitel, Pablo; Piccaluga, Francisco (Revista de la Asociación Argentina de Ortopedia y Traumatología, 2013)
1. Engelbrecht E, Heinert K. Klassifikation und Behandlungsrichtlinien von Knochensubsanzverlusten bei Revisionsoperationen am Huftgelenk mittelfrsige Ergebnisse. Primare und Revisionsalloarthroplastik Hrsg-Endo-Klinik, Hamburg: Springer-Verlag, Berlin; 1987:189. 2. Merle d’Aubigné R, Postel M. Functional results of hip arthroplasty with acrylic prosthesis. J Bone Joint Surg Am 1954;36:451. 3. Hood RW, Wright TM, Burstein AH. Retrieval analysis of total knee prostheses: a method and its application to 48 total condylar prostheses. J Biomed Mat Res 1983;17:829. 4. Carlsson AS, Gentz CF, Stenport J. Fracture of the femoral prosthesis in total hip replacement according to Charnley. Acta Orthop Scand 1977;48:650-5. 5. Chao EYS, Coventry MB. Fracture of the femoral component after total hip replacement. An analysis of fifty-eight cases. J Bone Joint Surg Am 1981;63:1078-94. 6. Charnley J. Fracture of femoral prostheses in total hip replacement. A clinical study. Clin Orthop 1975;111:105. 7. Buttaro M, Mayor M, Van Citters D, Piccaluga F. Fracture of a proximally modular, distally fluted uncemented implant with diaphyseal fixation. J Arthroplasty 2007;22(5):780-3. 8. Bohm P, Bischel O. Femoral revision with the Wagner SL revision stem: evaluation of one hundred and twenty-nine revisions followed for a mean of 4.8 years. J Bone Joint Surg Am 2001;83(7):1023. 9. Woolson ST, Milbauer JP, Bobyn JD, Yue S, Maloney WJ. Fatigue fracture of a forged cobalt-chromium-molybdenum femoral component inserted with cement. A report of ten cases. J Bone Joint Surg Am 1997;79(12):1842.